Exposure to tick bites in a university student community in Chihuahua, México - Chavarría-Bencomo, Inés Valeria; Español, Español; Español, Español; Español, Español; Español, Español; Español, Español (Acta Universitaria, 2023)
Chihuahua is one of the states with the highest number of rocky mountain spotted fever cases and ranks third in other rickettsiosis nationwide, both transmitted by tick bites. The objective of the present study was to evaluate, through a questionnaire, the history of exposure to tick bites in first-year university students in 2021 and 2022. In total, 2937 responses were obtained, of which 4.09% (n = 120/2937) reported bites. The risk of bite was higher in those who lived inside the municipality of Chihuahua; in students with a wooden patio, compared to those without a patio or with a concrete patio; in students who used miticides; and in those who reported rodents, fleas, ticks, or lice at home or at their block. The evaluation of the prevalence of tick bites and its association with sociodemographic characteristics can help identify risk factors in the population studied.